Bi-Directional Electric Vehicle (EVs) Charger - Ramkrushna Bhoyar, Ravina; D. Mujumdar, Dinesh (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
The goal of this project is to create an on-board bidirectional battery charger for Electric Vehicles (EVs) that can be used for Grid-to-Vehicle (G2V), Vehicle-to-Grid (V2G), and Vehicle-to-Home (V2H) technologies. The batteries are charged from the power grid with sinusoidal current and unitary power factor in the G2V operation mode. Computer simulations were used to validate the results, which were then confirmed by experimental data Instruction. The energy stored in the batteries may be utilized to power home loads during power outages or to power loads in areas where there is no access to the power grid in the V2H operation mode. The hardware structure of the bidirectional battery charger is given throughout the study, as well as the control algorithms. Some size concerns for the AC side passive filter are taken into account.